(untitled) (Impetus, 2021)
Violence is present in the educational environment, and the school life and partly the relations that are given between different actors that intervene in the educative act The following presentation raises the importance of generating ways of controlling the problemtic situations that appears in the educational institutions, from the physical activity it proposes to take a look in the multiple benefits that the physical practice generates. There is also a boarding of the different concepts of physical activity, benefit, physical exercise, protective factor, school life, prevention, intervention and innovation, that entail to identify parameters to generate intervention proposals, that reduce the conflict and the violence, that is generated in the educational environment by means of diagnoses that lead to the construction of educational programs from the recommendations of the World Health Organization. According to some studies the practice of physical activity and the exercise acts as a protective factor that manages to reduce the levels of aggressiveness, generates benefits during the childhood and the adolescence, in the growth, the maintenance of the caloric balance, the prevention of the factors of risk of cardiovascular diseases, the opportunity to develop social interactions, feelings of personal satisfaction and mental well-being.